Quantitative identification and spatial analysis of land use ecological-production-living functions in rural areas on China's southeast coast - Zou, Lilin; Liu, Yansui; Yang, Jianxin; Yang, Shengfu; Wang, Yongsheng; Cao zhi; Hu, Xuedong (Habitat international, 2020)
The quantitative identification of land use functions (LUFs) forms the basis of land use planning and management. Based on the widely recognized “ecological-production-living” function in sustainable development, a uniform classification and value evaluation system of LUFs for China's rural land use planning and management is established. To highlight the functions of ecological regulation, product supply and living security, the LUFs were divided into 8 primary functions and 20 subfunctions. LUF value evaluation function groups were established based on the indirect or direct value of land use. For empirical research, Fengzhou Town, a typical rural coastal area in southeastern China, was selected as an example. The results show that the values of the ecological, production and living functions account for 14.31%, 44.54% and 41.15% of the total value, respectively. This finding indicates that the primary direction of land use in the study area is oriented toward pursuing the production and living functions. The spatial distribution of the values of the production and living functions shows obvious consistency, and they are also clearly complementary with the ecological function. More than 90% of the land area is assigned double or triple functions, which indicates that the multifunctional characteristics of land use are significant, while the spatial function zoning is disordered. These findings are consistent with the socioeconomic development of the study area, demonstrating that the established classification and value evaluation system of LUFs can reliably reflect realistic land use and will provide scientific support for the multifunctional utilization and effective management of rural land in China.